Structuring of genetic diversity in Albizia gummifera C.A.Sm. among some East African and Madagascan populations - Nantongo, Judith S.; Okullo, John B. L.; Eilu, Gerald; Ramonta, Isabelle R.; Odee, David; Cavers, Stephen (African Journal of Ecology, 2010)
The fast-growing, leguminous tree Albizia gummifera C.A.Sm. (Fabaceae, Mimosoideae) is a potentially useful species for ecological restoration of degraded forests. The species has multifunctional benefits such as timber, forage and medicine. However, it also has the potential to restore degraded soils as it forms mycorrhizal and rhizobial symbiotic associations (Hall, 2004), meaning ecological and economic benefits would be obtained simultaneously.A key consideration in forest restoration is ensuring sustainability of the restored habitat, for which maximizing the suitability of planting material is important. In tree species, high levels of within-population genetic diversity and local adaptation are common phenomena. However, the strength and relative extent of local versus regional genetic structuring varies with species and depends on particular characteristics of life history (such as longevity, dispersal mechanisms and successional stage). Therefore if genetic hazards (e.g. maladaptation, inbreeding ⁄ outbreeding depression) are to be taken into account, species must be considered individually.
Keywords: genetic diversity; gummifera